Analysis of Olive Oil Mill Wastewater from Conventionally Farmed Olives: Chemical and Microbiological Safety and Polyphenolic Profile for Possible Use in Food Product Functionalization - Lino Sciurba; Serena Indelicato; Raimondo Gaglio; Marcella Barbera; Francesco Paolo Marra; David Bongiorno; Salvatore Davino; Daniela Piazzese; Luca Settanni; Giuseppe Avellone (Foods)
This study aimed to perform an in-depth investigation of olive oil mill wastewater (OOMW). Two OOMW samples (OOMW-A and OOMW-B) from conventionally farmed olives were collected from two different olive oil mills in Palermo province (Italy). Multiresidual analysis indicated that both OOMW samples were unsuitable for food production due to pesticide residues. Specifically, OOMW-A contained 4 active compounds totaling 5.7 μg/L, while OOMW-B had 16 analytes with a total content of 65.8 μg/L. However, polyphenol analysis in the OOMW revealed 23 compounds with high concentrations of hydroxytyrosol, secoiridoid derivatives, phenolic acids, flavones, and total polyphenol content ranging from 377.5 μg/mL (for OOMW-B) to 391.8 μg/mL (for OOMW-A). The microbiological analysis of OOMW samples revealed only detectable viable bacteria (102 CFU/mL) of the lactic acid bacteria (LAB) group. Two distinct LAB strains, Lactiplantibacillus plantarum OMW1 and Leuconostoc mesenteroides OMW23, were identified. These strains demonstrated notable acidification capabilities and produced antibacterial compounds. In conclusion, despite the high polyphenolic content and microbiological suitability of OOMW, the presence of micro-contaminants hinders their use in food production. Thus, further studies are underway to investigate OOMW from organically farmed olives for bakery product functionalization, employing the two selected LAB strains resistant to olive polyphenols as leavening agents.